Evaluation of the structure of the services sector in Brazil: a regional approach - Verônica Cardoso; Fernando Perobelli (European Regional Science Association (ERSA), 2014)
The accelerated growth of the service sector is one of the characteristics of the actual pattern of global growth. In Brazil, it is possible to point to a move towards a 'service economy' following the global standard. However, it cannot say that Brazil is regionally services intensive, ie, the national pattern of development of the sector cannot be seen in all regions of the country. In the same way, the regional development is not uniform throughout the country; the development of the service sector also is not. That is what this study aims to assess. The service sector taking into account the spatial and structural characteristics. Thus, the main aim is divided into four parts: 1) establish a functional inter-regional hierarchy and understand the influence of services in the Brazilian urban polarization process; 2) understand and map the productive structure of the service sectors in Brazil from hierarchy built; 3) analyzing the intrinsic relationship between the industrial and service sectors; and 4) understand the process of growth of services sectors identifying agglomerative constraints that influence this process. The study used a data from 1995 and 2011 for Brazilian municipalities and grouped a number of methodologies strategies to reach the goals. Starting with a regionalization methodology to define the poles of concentrators services and their regions of influence, through an analysis of the production structure and income of the service sectors from variables constructed that characterize these regions, ending with a spatial econometric model which seeks to understand the growth of the service sector from these variables. The results indicate that the Brazilian regional setting, as regards the ability of polarization from the service sector, has not undergone very significant changes, with service activities, ie, the central goods, concentrated in the same large pole that 20 years ago and these same large pole polarizing large regions that also have changed little. The results also indicate a spatial pattern of distribution of services sectors. There is a North-South pattern of concentration of sectors. The South representing concentration of the most dynamic sectors and providing greater diversity of services, as well as larger sizes of firm, ie, greater economies of scale. Already the north axis of the country, especially the influence areas located in the northeast region, showed lower diversification of services and a strong concentration of 'Public Administration' sector. It was also possible to note that the hypothesis of agglomeration and scale population contributing to the development of the service sector was reaffirmed, as well as an eventual correlation between industrial activity and service activity more densely.
Keywords: L80; L89; O14; R12; C31; 330; Service sector; regional development; Brasilian economy; structural analysis